Author Correction: Potential role of compost mixed biochar with rhizobacteria in mitigating lead toxicity in spinach - Zafar-Ul-Hye, Muhammad; Tahzeeb-Ul-Hassan, Muhammad; Abid, Muhammad; Fahad, Shah; Brtnicky, Martin; Dokulilova, Tereza; Datta, Rahul; Danish, Subhan (Scientific reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.